PENGARUH MUSIK PADA LATIHAN BEBAN DALAM MENINGKATKAN KEKUATAN OTOT BAHU (DELTOID) DAN PUNGGUNG (LASTTISIMUSDORSI) MEMBER FIK FITNESS CENTER TAHUN 2018/2019 (Indonesian Journal for Physical Education and Sport, 2021)
Norma Zunika Prasetiawan. 2019. The Effect of Music Play in Weightlifting Exercise to Improve Muscle Strength in Year 2018/2019. A Final Project. The Department of Physical Education, Health and Recreation; The Faculty of Sports Sciences; Universitas Negeri Semarang. Advisor: Dr. Tri Rustiadi, M.Kes. Key Word : Influence, Music, Muscle, The research question of this research is how the effect of music play in weightlifting exercise to improve muscle strength of FIK fitness center members in the year 2018/2019 is. The research is aimed to reveal and to analyze the fitness members’ muscle strength in which the exercise room play and do not play music. This is a descriptive quantitative research with purposive sampling technique was employed in selecting the samples based on certain condition. Members’ background equalization was done to help minimalizing or even deleting extraneous variables which may drive into unreliable result. There were 12 selected samples for the research. The members were divided into two groups which were experiment group one and experiment group two. The experiment group one got music play with them, while the experiment group two was the other hand. The pre-test identification of thrust to experiment group one, to whom the music was played, resulted the thrust mean point in 25.33, highest achieved point in 29 and lowest achieved point in 20. On further identification, the thrust post-test resulted mean point in 34.67, highest achieved point in 40, and lowest achieved point in 30. For the pull section identification, the pre-test resulted mean point in 22.67, highest achieved point in 34 and lowest achieved point in 14. The post-test resulted mean point in 31.50, highest achieved point in 45 and lowest achieved point in 20. The experiment group two whom music did not play to, on the other side shown different progress. For the thrust section identification, the pre-test resulted mean point in 23.33, highest achieved point in 29 and the lowest achieved point in 15. The post-test resulted mean point in 26.33, highest achieved point in 32 and lowest achieved point in 17. For the pull section identification, the pre-test resulted mean point in 20.50, highest achieved point in 29, and lowest achieved point in 14. The post-test resulted mean point in 23.33, highest achieved point in 32 and the lowest achieved point in 18.